Influence of electrode spacing and gas pressure on parameters of a runaway electron beam generating during the nanosecond breakdown in SF6 and nitrogen. Issue 2 (31st May 2017) - Tarasenko, Victor F.; Zhang, Cheng; Kozyrev, Andrey V.; Sorokin, Dmitry A.; Hou, Xingmin; Semeniuk, Natalya S.; Burachenko, Alexander G.; Yan, Ping; Kozhevnikov, Vasily Yu.; Baksht, Evgenii Kh.; Lomaev, Mikhail I.; Shao, Tao
Abstract : This study deals with experimental and theoretical simulation data showing the influence of electrode spacing and gas pressure on parameters of a supershort avalanche electron beam (SAEB) formed in SF6 and nitrogen at different rise times and amplitudes of a voltage pulse. Using GIN‐55‐01, VPG‐30‐200, and SLEP‐150M pulsers, tubular cathodes with a diameter of 6 mm, as well as gaps of 3, 5, and 8 mm, it was shown that the SAEB current amplitude can both increase and decrease depending on an electrode spacing, a waveform and a rise time of the voltage pulse, as well as the pressure of SF6 and nitrogen. It was established as a result of simulation that maximal voltage across the gap during the process of generation of runaway electrons and the thickness of an anode foil have a major effect on the SAEB current pulse amplitude.